2021
DOI: 10.1016/j.metabol.2021.154739
|View full text |Cite
|
Sign up to set email alerts
|

The serum metabolome of COVID-19 patients is distinctive and predictive

Abstract: Background Metabolism is critical for sustaining life, immunity and infection, but its role in COVID-19 is not fully understood. Methods Seventy-nine COVID-19 patients, 78 healthy controls (HCs) and 30 COVID-19-like patients were recruited in a prospective cohort study. Samples were collected from COVID-19 patients with mild or severe symptoms on admission, patients who progressed from mild to severe symptoms, and patients who were followed from hospital admission to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
91
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 44 publications
16
91
2
Order By: Relevance
“…Previous studies revealed that COVID-19 patients during the infection period had metabolic abnormalities in TCA cycle, purine and lipid metabolism. [11][12][13][14]19 In our study, we found that these pathways remained disturbed in the recovered COVID-19 patients 3 months after discharge when compared with HCs, especially in the RCs, which suggests that metabolic abnormalities in COVID-19 patients failed to fully return to normal levels even 3 months after discharge from the hospital.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Previous studies revealed that COVID-19 patients during the infection period had metabolic abnormalities in TCA cycle, purine and lipid metabolism. [11][12][13][14]19 In our study, we found that these pathways remained disturbed in the recovered COVID-19 patients 3 months after discharge when compared with HCs, especially in the RCs, which suggests that metabolic abnormalities in COVID-19 patients failed to fully return to normal levels even 3 months after discharge from the hospital.…”
Section: Discussionmentioning
confidence: 56%
“…10 Recent studies have revealed that metabolic dysregulation in COVID-19 patients and metabolites may help stratify patients in terms of disease severity during hospitalisation. [11][12][13][14][15][16][17] Moreover, it has been reported that after discharge, only one-third of the metabolites were recovered, 14 and some metabolites continued to be abnormal in recovered COVID-19 patients. 18,19 In addition, we recently found that discharged patients with pulmonary sequelae also had disordered plasma metabolite profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have also explored how the presence of these comorbidities influences the metabolomics differences found in COVID-19 patients concerning healthy controls and patients with different severity grades. Shi et al [ 83 ] compared the serum metabolome profiles of COVID-19 patients with and without comorbidities. The results showed that none of the groups of patients with hypertension, diabetes or fatty liver disease could be distinguished from patients without comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolome was assayed as described previously ( 16 , 17 ). Briefly, 20 mg of feces or 200 μL of the serum was added to 800 μL of precooled chromatography grade methanol (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%